A quantitative quantum-chemical analysis tool for the distribution of mechanical force in molecules - Neudecker, Tim; Dreuw, Andreas (The journal of chemical physics, 2014)
The promising field of mechanochemistry suffers from a general lack of understanding of the distribution and propagation of force in a stretched molecule, which limits its applicability up to the present day. In this article, we introduce the JEDI (Judgement of Energy DIstribution) analysis, which is the first quantum chemical method that provides a quantitative understanding of the distribution of mechanical stress energy among all degrees of freedom in a molecule.
Gesehen am 15.12.2017